Analisis Penyebab Kerusakan Hot Rooler Table dengan Menggunakan Metode Failure Mode And Effect Analysis (FMEA) - Anthony, Muhamad Bob (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2018)
This research was conducted in an international company engaged in iron and steel products manufacturing industries. One of the equipment that is often damaged is a hot roller table machine in the furnace section mill unit. The availability results obtained in hot roller table equipment is 96.571% and is still below the company standard which is set at 98%. Therefore, we need an analysis of the root causes of the problem and search for the best solution to fix the existing problem by applying the method of Failure Mode and Effect Analysis (FMEA). FMEA is a method that can systematically and structurally analyze and identify the consequences of a system or process failure, and also reduce or analyze the probability of failure. The purpose of this study is to identify and analyze the level of damage and its causes with the application of the FMEA method. Based on the pareto diagram the damage to the hot roller table machine, it was found that the highest frequency of damage was in the rotary coupling with a down time percentage of 26.9%. From the FMEA Analysis, two components that have very high RPN values are categorized as potential severit i.e. bearing as the first with an RPN value of 392 and the second is a seal ring with an RPN value of 294. The two components are the main priority for repair of the furnace section. mill, especially for machine and human aspects.